Visuomotor Resolution in Telerobotic Grasping with Transmission Delays - Afgin, Omri; Sagi, Nir; Nisky, Ilana; Ganel, Tzvi; Berman, Sigal (Frontiers in Robotics and AI, 2017)
Weber’s law is among the basic psychophysical laws of human perception. It determines that human sensitivity to change along a physical dimension, the just noticeable difference (JND), is linearly related to stimulus intensity. Conversely, in direct (natural), visually-guided grasping, Weber’s law is violated, and the JND does not depend on stimulus intensity. The current work examines adherence to Weber’s law in telerobotic grasping. In direct grasping, perception and action are integrated for task performance. Conversely, in telerobotic control, there is an inherent spatial and temporal separation between perception and action. The understanding of perception-action association in such conditions may facilitate development of objective measures of telerobotic systems and contribute to improved interface design. Moreover, telerobotic systems offer a unique platform for examining underlying causes for the violation of Weber’s law during direct grasping. We examined whether, like direct grasping, telerobotic grasping with transmission delays violates Weber’s law. To this end, we examined perceptual assessment, grasp control, and grasp demonstration, using a telerobotic system with time delays in two spatial orientations: alongside and facing the robot. The examination framework was adapted to telerobotics from the framework used for examining Weber’s law in direct grasping. The variability of final grip apertures in perceptual assessment increased with object size in adherence with Weber’s law. Similarly, the variability of maximal grip apertures in grasp demonstration approached significance in adherence with Weber’s law. In grasp control, the variability of maximal grip apertures did not increase with object size, which seems to violate Weber’s law. However, unlike in direct grasping, motion trajectories were prolonged and fragmented, and included an atypical waiting period prior to finger closure. Therefore, in this condition, maximal grip aperture was an inappropriate indicator of JND. Instead, we calculated the aperture at the end of the opening phase, the initial grip aperture, and the final grip aperture at the beginning of the waiting period, as more appropriate JND indicators. The initial grip apertures adhered to Weber’s law. The final grip apertures approached significance in the same direction. This suggests that perception-action association during telerobotic grasping with transmission delays significantly diverge from direct grasping.